1995
DOI: 10.1063/1.358911
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus-vacancy-related deep levels in GaInP layers

Abstract: Deep levels in lattice-matched Ga0.51In0.49P/GaAs heterostructure have been investigated by thermal-electric effect spectroscopy (TEES) and temperature-dependent conductivity measurements. Four samples were grown by molecular-beam epitaxy with various phosphorus (P2) beam-equivalent pressures (BEP) of 0.125, 0.5, 2, and 4×10−4 Torr. A phosphorus vacancy (VP) -related deep level, an electron trap, was observed located at EC−0.28±0.02 eV. This trap dominated the conduction-band conduction at T≳220 K and was resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…27 DLTS studies have reached a variety of different conclusions regarding the origin of the low temperature peak in GaInP, such as cation vacancies ͑SSMBE material 28 ͒, a dopant related DX center ͑MBE material 29,30 ͒, interstitial phosphorus ͑liquid phase epitaxial material 31 ͒ and phosphorus vacancies ͑MBE͒. 32 The observations of Kwon et al 33 showed that the emission rate of the N1 peak is affected by the type of dopant ͑S, Se, and Te were tested͒ suggesting it to be a complex. To investigate this further, the rate of increase of the N1 peak was measured using the same method as in our previous work on N3 3 .…”
Section: P Vacancy As the Midgap Deep Levelmentioning
confidence: 99%
“…27 DLTS studies have reached a variety of different conclusions regarding the origin of the low temperature peak in GaInP, such as cation vacancies ͑SSMBE material 28 ͒, a dopant related DX center ͑MBE material 29,30 ͒, interstitial phosphorus ͑liquid phase epitaxial material 31 ͒ and phosphorus vacancies ͑MBE͒. 32 The observations of Kwon et al 33 showed that the emission rate of the N1 peak is affected by the type of dopant ͑S, Se, and Te were tested͒ suggesting it to be a complex. To investigate this further, the rate of increase of the N1 peak was measured using the same method as in our previous work on N3 3 .…”
Section: P Vacancy As the Midgap Deep Levelmentioning
confidence: 99%
“…The concentration of P1 and P2 in undoped InGaP decreased with increasing P2 BEP, suggesting that these traps may be associated with the crystal defects in the P deficient lattice sites such as the phosphorus vacancies(V,). Also, the origin of P3 and P4 signals were attributed to phosphorus vacancies V, andior a transformed defect from V, such as a Gap or In, antisite [5]. After hydrogenation at 200 "C for 2 h, the relative intensities of all traps decreased in about 10 times and only two signals corresponding to P3 and P4 traps around 180 K and 280 K remained as main defects.…”
Section: Resultsmentioning
confidence: 95%
“…These states in alloys have been widely studied during recent years (see e.g. [1][2][3][4][5] and references therein) for the cases of Coulombic and short-range potential defects. The latter case is typical for states localized on structure imperfections or on substitutional impurities.…”
Section: Introductionmentioning
confidence: 99%